Pengaruh Komunikasi Interpersonal, Koordinasi dan Budaya Organisasi Terhadap Kinerja Pegawai Kecamatan Bogor Tengah Kota Bogor - Hadi, Sopyan; Ermanto, Conrita; Ali, Akbar (ANTASENA: Governance and Innovation Journal, 2024)
The aim of this research is to determine and analyze the influence of interpersonal communication, coordination and organizational culture individually and together on the performance of employees in Bogor Tengah District, Bogor City. The research method uses a survey with a descriptive quantitative approach. The sampling technique is a saturated sample or census, which is a sample research technique when all members of the population are used as samples. The number of samples in this study was 30 respondents. The research results show: a) From the results of the research analysis, interpersonal communication variables influence employee performance, namely that there is an influence size of 51.1%. The results of hypothesis testing show that interpersonal communication has a positive and significant effect on employee performance in Bogor Tengah District, Bogor City. This means that hypothesis Ha1 (accepted). b) From the results of the research analysis, the coordination variable has an effect on work productivity, namely that there is an influence size of 52.4%. The results of the hypothesis test show that coordination has a positive and significant effect on employee performance in Bogor Tengah District, Bogor City. This means that the hypothesis Ha2 (accepted). c) From the results of the research analysis, organizational culture variables influence employee performance, namely that there is an influence size of 54.5%. The results of hypothesis testing show that organizational culture has a positive and significant effect on employee performance in Bogor Tengah District, Bogor City. This means that hypothesis Ha3 (accepted). d) From the results of the research analysis, the variables of interpersonal communication, coordination and organizational culture together have an influence on employee performance, namely there is an influence size of 60.1%. The results of hypothesis testing show that interpersonal communication, coordination and organizational culture together have a positive and significant effect on employee performance in Bogor Tengah District, Bogor City. This means that hypothesis Ha4 (accepted).